Automation of Design & Modeling Aspects of Bush-Pin Coupling. Issue 1 (April 2021) - Rajput, Sandeep; Sharma, Rajkumar; Kumar, Mohit
Abstract: As we know that the coupling is a device used for transmitting high torque from one shaft to another in industrial applications. In this paper designing and modeling of bush-pin coupling has been performed. The software MS-Excel, CATIA V5R20, and MATLAB are utilized for designing, modeling, and simulating the bush-pin coupling. The design and modeling process has been automated by the synchronization with MS-Excel and CATIA V520. This automated process will be helpful in the understanding concept of designing and modeling by the researcher and industrial experts. This process will also save time and energy which will be helpful in optimization of different input parameters to achieve high torque at low investment.